Visual analysis of environmental research progress in Germany linking Development Anthropology: A sustainable approach based on the Web of Science - Zong, Wei; Wang, Fei; Tu, Bo; Tu, Huazhong; Zhang, Hao; Wu, Chuke; Toseef, Muhammad (Frontiers in Psychology, 2023)
Environmental devaluation is a major concern for European countries as they seek to scrutinize strategies for development anthropology. Germany holds diversified ties with the socioeconomic and environmental development of the region. In accordance with global obligations, Germany's research on environmental issues, protection laws and actions, and universities and scientific research institutions in the field of environmental protection are progressing toward the development of a sustainable future securing the development anthropology. However, Germany's research on environmental issues is unclear to the rest of the world. Chinese scholars also lack effective countermeasures and suggestions for implementing environmental protection cooperation between China and Germany under the Belt and Road Initiative to draw a sustainable global drain. Understanding the current situation and frontier trend of environmental research in German academic circles is essential and irreplaceable for relying on research results data and quantitative analysis theory to carry out the research process. The methodology of this paper established a quantitative analysis based on “institutions,” “scholars,” “research objects,” and “frequency of keywords” among the research results on environmental issues in Germany. It constructs a digital portrait of the field of environmental research in Germany. Knowledge mapping is extensively used in this study as the primary research tool to show the development of environmental research in Germany. The standard deviation of social science research has roughly doubled in that time. CiteSpace, a visual tool for document statistical analysis, is used to analyze the research results on environmental protection published by German scholars from 2008 to 2018. The study results include Web of Science Network, and finally, a visual map is drawn. This study analyzes the status quo, research institutions, keywords, research hotspots, and research trends of international cooperation in environmental research in Germany. The findings are in supportive position of environment study that is the key to human existence and societal development. Leading to this Germans are in concern of human anthropology being reflected in scholarly published work. In response to practical challenges, “global warming” and “sustainable development” became the most frequently used keywords. It provides sustainable thoughts and countermeasures to strengthen Sino-German environmental protection exchange and cooperation further.